Dermatofibrosarcoma Protuberans and Adjuvant Radiotherapy: A Case Report with Uncertain Surgical Margins in The Breast - Arslan, Alaettin; Karagoz Eren, Saliha; Ozcan, Serdal Sadet; Akay, Ebru; Ozdemir, Mustafa (Archives of Breast Cancer, 2021)
Background: Dermatofibrosarcoma Protuberans (DFSP) is a rare, locally aggressive superficial soft tissue tumor that can occur in many parts of the body. Surgical resection with a wide margin of safety is the main treatment modality of this rare tumor of the breast. According to the postoperative pathology report, the patient can be followed up or adjuvant radiotherapy (RT) can be added. Case presentation: A 22-year-old woman presented with a mass filling the lower inner quadrant of her right breast. Tru-cut biopsy revealed a mesenchymal tumor, but excision was recommended for definitive diagnosis. A right breast quadrantectomy was performed. The result came as DFSP. Tumor diameter was 10x9x6.5 cm and the tumor was positive in most of the surgical margins. The patient underwent re-resection and a residual tumor with a diameter of 0.2 cm was detected at a distance of 3.3 cm from the surgical margin. Although the surgical margins were negative, the distance of the posterior surgical margin, in particular, could not be assured. Because of the uncertainty of surgical margins, 60 Gy RT was planned. Conclusion: The localization of DFSP in the breast is extremely rare and surgery is the primary treatment. RT should be added as an adjuvant when safe surgical margins cannot be obtained.